Antecedents-Consequences Modification to Decrease Hyper-activity and Improve Attention of Child with ADHD - Kusuma Wijayanti, Puspita Adhi; Cahyadi, Surya (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
The prevalence of ADHD children increases every year. Some researchers have shown that psychosocial behavior therapy (antecedents-consequences modification) was effective to decrease hyperactivity and increase attention to ADHD children. This study aims to find out the effectiveness of antecedents-consequences modification by parents and teachers to decrease hyperactivity and increase attention to a 6 years old boy with ADHD. The study was a single case experimental design. Psychosocial behavior therapy has been used with antecedents-consequences modification. The antecedents-consequences modification was applied by teacher at school and parents at home. Data were analyzed using Wilcoxon Signed Rank Test. Results showed that there’s a significant decrease of hyperactivity behavior and significant increase of doing his assignment both at school and also at home. Not only about the content of behavior therapy itself, but how to give the therapy is important. Parents and teacher should do the therapy consistently, immediately, specifically and saliency to reach the target of intervention. Keywords: ADHD Children, Antecedents, Consequences, Modification Reference: (APA), A. A. P. (2013). Diagnostic and Manual of Mental Disorder (5th ed.). Arlington: American Psychiatric Association. Amalia, R. (2018). Intervensi terhadap Anak Usia Dini yang Mengalami Gangguan ADHD Melalui Pendekatan Kognitif Perilaku dan Alderian Play Therapy. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2(1), 27. https://doi.org/10.31004/obsesi.v2i1.4 Anastopoulos, A.D; Farley, S. . (2003). A Cognitive Behavioural Training Program for Parents of Children with Attention-Deficit/Hyperactivity Disorder. In W. J. Kazdin, Alan E (Ed.), Evidence-based psychotherapies for children and adolescents (pp. 187–203). New York: Guildford Press. Barkley, Russell A; DuPaul, G.L ; McMurray, M. . (1990). A comprehensive evaluation of attention deficit disorder with and without hyperactivity. Journal of Consulting and Clinical Psychology, 58, 775–789. Barkley, R. A. (2006). Attention-deficit hyperactivity disorder : A handbook for diagnosis and treatment (3rd ed.). New York City: Guildford Press. Barlow, D.H ; Hersen, M. (1984). Single case experimental design : Strategies for studying behavior change (2nd ed.). New York: Pergamon Press. Baumeister, S., Wolf, I., Holz, N., Boecker-Schlier, R., Adamo, N., Holtmann, M., … Brandeis, D. (2018). Neurofeedback Training Effects on Inhibitory Brain Activation in ADHD: A Matter of Learning? Neuroscience, 378, 89–99. https://doi.org/10.1016/j.neuroscience.2016.09.025 Cantwell, D. P., & Baker, L. (1991). Association between attention deficit-hyperactivity disorder and learning disorders. Journal of Learning Disabilities, 24(2), 88–95. https://doi.org/10.1177/002221949102400205 Center for Children and Families. (2019). Evidence-based Psychosocial Treatment for ADHD Children and Adolescents. Retrieved from http://ccf.fiu.edu Davidson, G. C. (2010). Abnormal Psychology. New Jersey: Wiley. DuPaul, George; Stoner, G. (2003). ADHD in the schools. New York: Guildford Press. DuPaul, G., & Weyandt, L. (2006). School-based intervention for children with attention deficit hyperactivity disorder: Effects on academic, social, and behavioural functioning. International Journal of Disability, Development and Education, 53(2), 161–176. https://doi.org/10.1080/10349120600716141 Erinta, D. B. M. S. (2012). Efektivitas penerapan terapi permainan sosialisasi untuk menurunkan perilaku impulsif pada anak dengan attention deficit hyperactive disorder (ADHD). Jurnal Psikologi : Teori & Terapan, 3(1). Evans, Steven W; Owens, Julie; Bunford, M. N. (2014). Evidence-Based Psychosocial Treatments for Children and Adolescents with Attention-Deficit/Hyperactivity Disorder. Journal Clinical Child Adolescence Psychology, 43(4), 527–551. https://doi.org/10.1038/jid.2014.371 Fabiano, G. A., Pelham, W. E., Coles, E. K., Gnagy, E. M., Chronis-Tuscano, A., & O’Connor, B. C. (2009). A meta-analysis of behavioral treatments for attention-deficit/hyperactivity disorder. Clinical Psychology Review, 29(2), 129–140. https://doi.org/10.1016/j.cpr.2008.11.001 Gerdes, A. C., Hoza, B., & Pelham, W. E. (2003). Attention-deficit/hyperactivity disordered boys’ relationships with their mothers and fathers: Child, mother, and father perceptions. Development and Psychopathology, 15(2), 363–382. https://doi.org/10.1017/S0954579403000208 Haas, S. M., Waschbusch, D. A., Pelham, W. E., King, S., Andrade, B. F., & Carrey, N. J. (2011). Treatment response in CP/ADHD children with callous/unemotional traits. Journal of Abnormal Child Psychology, 39(4), 541–552. https://doi.org/10.1007/s10802-010-9480-4 Helseth, S. A., Waschbusch, D. A., Gnagy, E. M., Onyango, A. N., Burrows-MacLean, L., Fabiano, G. A., … Pelham, W. E. (2015). Effects of behavioral and pharmacological therapies on peer reinforcement of deviancy in children with ADHD-Only, ADHD and conduct problems, and controls. Journal of Consulting and Clinical Psychology, 83(2), 280–292. https://doi.org/10.1037/a0038505 Hidayati, DM Ria ; Purwandari, E. (2010). Time Out : Alternatif Modifikasi Perilaku Anak ADHD (Attention Deficit/ Hyperacitivity Disorder). Indigenous, Jurnal Ilmiah Berkala Psikologi, 12(2), 101–114. Hinshaw, S. P., Owens, E. B., Wells, K. C., Kraemer, H. C., Abikoff, H. B., Arnold, L. E., … Wigal, T. (2000). Family processes and treatment outcome in the MTA: Negative/ineffective parenting practices in relation to multimodal treatment. Journal of Abnormal Child Psychology, 28(6), 555–568. https://doi.org/10.1023/A:1005183115230 Hinshaw, Stephen P., Owens, E. B., Zalecki, C., Huggins, S. P., Montenegro-Nevado, A. J., Schrodek, E., & Swanson, E. N. (2012). Prospective follow-up of girls with attention-deficit/hyperactivity disorder into early adulthood: Continuing impairment includes elevated risk for suicide attempts and self-injury. Journal of Consulting and Clinical Psychology,80(6), 1041–1051. https://doi.org/10.1037/a0029451 Jackson, N. A. (2003). A Survey of Music Therapy Methods and Their Role in the Treatment of Early Elementary School Children with ADHD. Journal of Music Therapy, 40(4), 302–323. https://doi.org/10.1093/jmt/40.4.302 Johnston, Charlotte; Mash, E. J. (2001). Families of Children With Attention-Deficit/Hyperactivity Disorder : Review and Recommendations for Future Research. Clinical Child and Family Psychology Review, 4(3), 183–207. Jr, W. E. P., Fabiano, G. A., & Pelham, W. E. (2008). Evidence-Based Psychosocial Treatments for Attention- Deficit / Hyperactivity Disorder (Vol. 4416). https://doi.org/10.1080/15374410701818681 Kaiser, N. M., McBurnett, K., & Pfiffner, L. J. (2011). Child ADHD severity and positive and negative parenting as predictors of child social functioning: Evaluation of three theoretical models. Journal of Attention Disorders, 15(3), 193–203. https://doi.org/10.1177/1087054709356171 Kazdin, A. E. (1984). Behavior Modification in Applied Settings. New York: Dorsey Press. Krasny-Pacini, A., & Evans, J. (2018). Single-case experimental designs to assess intervention effectiveness in rehabilitation: A practical guide. Annals of Physical and Rehabilitation Medicine, 61(3), 164–179. https://doi.org/10.1016/j.rehab.2017.12.002 Langberg, J. M., Molina, B. S. G., Arnold, L. E., Epstein, J. N., Altaye, M., Hinshaw, S. P., … Hechtman, L. (2011). Patterns and predictors of adolescent academic achievement and performance in a sample of children with attention-deficit/hyperactivity disorder. Journal of Clinical Child and Adolescent Psychology, 40(4), 519–531. https://doi.org/10.1080/15374416.2011.581620 Nigg, J.T ; Barkley, R. . (2014). (Attention-deficit Hyperactivity Disorder). In R. A. Barkley (Ed.), E-book Pediatric เรื่องPsychiatry (Third Edit, Vol. 54, pp. 1–17). Retrieved from http://www.thaipediatrics.org/pages/Doctor/Download/48aedb8880cab8c45637abc7493ecddd:e0a186938dc3b74657fd46d32fac5fe6 Pastor, P., Reuben, C., Duran, C., & Hawkins, L. J. (2015). Association between diagnosed ADHD and selected characteristics among children aged 4-17 years: United States, 2011-2013. NCHS Data Brief, (201), 201. Patterson, G. . (1982). Coercive Family Process. Eugene: Castalia. Pfiffner, L. J ; Barkley, R. . (1990). Educational Placement and Classroom Management. In R. A. Barkley (Ed.), Attention Deficit Hyperactivity Disorder : A Handbook for Diagnosis and Treatment. New York: Guildford Press. Pfiffner, Linda J; Barkley, R; DuPaul, G. (2006). Treatment of ADHD in school settings. In R. A. Barkley (Ed.), Attention-deﬁcit hyperactivity disorder: A handbook for diagnosis and treatment (3th ed., pp. 547–589). New York: Guildford Press. Pfiffner, L. J., Calzada, E., & McBurnett, K. (2000). Interventions to enhance social competence. Child and Adolescent Psychiatric Clinics of North America, 9(3), 689–709. https://doi.org/10.1016/s1056-4993(18)30113-5 Pfiffner, Linda J., Hinshaw, S. P., Owens, E., Zalecki, C., Kaiser, N. M., Villodas, M., & McBurnett, K. (2014). A two-site randomized clinical trial of integrated psychosocial treatment for ADHD-inattentive type. Journal of Consulting and Clinical Psychology, 82(6), 1115–1127. https://doi.org/10.1037/a0036887 Pfiffner, Linda J, & Haack, L. M. (2014). Behavior Management for School - Aged Children with ADHD. 23, 731–746. Pfiffner, Linda J, Hinshaw, S. P., Owens, E., Zalecki, C., Kaiser, N. M., Villodas, M., & Mcburnett, K. (2015). A two-site randomized clinical trial of Integrated Psychosocial Treatment for ADHD-Inattentive Type. Journal of Consulting and Clinical Psychology, 82(6), 1115–1127. https://doi.org/10.1037/a0036887.A Riddle, M. A., Yershova, K., Lazzaretto, D., Paykina, N., Yenokyan, G., Greenhill, L., … Posner, K. (2013). The preschool attention-deficit/hyperactivity disorder treatment study (PATS) 6-year follow-up. Journal of the American Academy of Child and Adolescent Psychiatry, 52(3). https://doi.org/10.1016/j.jaac.2012.12.007 Saputro, D. (2009). ADHD (Attention Deficit/ Hyperactivity Disorder). Jakarta: Sagung Seto. Schunk, D. H. (2012). Learning Theories : An Educational Perspective (6th ed.; Pearson Education, Ed.). Boston. Shriver, M. D., Segool, N., & Gortmaker, V. (2011). Behavior observations for linking assessment to treatment for selective mutism. Education and Treatment of Children, 34(3), 389–411. https://doi.org/10.1353/etc.2011.0023 Suyanto, B. N., & Wimbarti, S. (2019). Program Intervensi Musik terhadap Hiperaktivitas Anak Attention Deficit Hyperactivity Disorder (ADHD). Gadjah Mada Journal of Professional Psychology (GamaJPP), 5(1), 15. https://doi.org/10.22146/gamajpp.48584 Taylor, E. (2009). Developing ADHD. Journal of Child Psychology and Psychiatry, 50, 126–132. Thomas, R., Sanders, S., Doust, J., Beller, E., & Glasziou, P. (2015). Prevalence of attention-deficit/hyperactivity disorder: A systematic review and meta-analysis. Pediatrics, 135(4), e994–e1001. https://doi.org/10.1542/peds.2014-3482 Tran, J. L. A., Sheng, R., Beaulieu, A., Villodas, M., McBurnett, K., Pfiffner, L. J., & Wilson, L. (2018). Cost-Effectiveness of a Behavioral Psychosocial Treatment Integrated Across Home and School for Pediatric ADHD-Inattentive Type. Administration and Policy in Mental Health and Mental Health Services Research, 45(5), 741–750. https://doi.org/10.1007/s10488-018-0857-y Tresco, K. E., Lefler, E. K., & Power, T. J. (2010). Psychosocial Interventions to Improve the School Performance of Students with Attention-Deficit/Hyperactivity Disorder. Mind & Brain : The Journal of Psychiatry, 1(2), 69–74. Retrieved from http://www.ncbi.nlm.nih.gov/pubmed/21152355%0Ahttp://www.pubmedcentral.nih.gov/articlerender.fcgi?artid=PMC2998237 U.S. Department of Health and Human Services. (2014). US Department of Health and Human Services. The Health and Well-Being of Children: A Portrait of States and the Nation, 2011-2012. (June), 1–109. Weiss, Gabrielle ; Hechtman, L. T. (1993). Hyperactive Children Grown Up. New York: Guildford Press.